Made in the U.S.A.? A Study of Firm Responses to Domestic Production Incentives - LESTER, REBECCA (Journal of Accounting Research, 2019)
ABSTRACT How do U.S. companies respond to incentives intended to encourage domestic manufacturing? I study the Domestic Production Activities Deduction (DPAD), which was enacted in the American Jobs Creation Act (AJCA) of 2004 and was the third largest U.S. corporate tax expenditure as of 2017. Using confidential data from the U.S. Bureau of Economic Analysis, I find greater average domestic investment spending of 95.5–143.6 million, but only within the sample of domestic‐only firms and not until 2010, when the greatest statutory DPAD benefits were available. Additional evidence suggests that U.S. multinational claimants invest abroad rather than in the United States and that the increased investment by DPAD firms is accompanied by a reduction in the domestic workforce, consistent with a substitution of capital for labor. I also show that the delayed investment response is due to firms engaging in other responses first, such as changing corporate reporting to shift income across time and borders. Quantifying the extent of these effects contributes to the literature that studies this tax deduction and informs policy makers as to the effectiveness of both manufacturing incentives and U.S. corporate income tax rate reductions in stimulating real domestic activity.